Role of elastin peptides and elastin receptor complex in metabolic and cardiovascular diseases. (11th April 2019) - Wahart, Amandine; Hocine, Thinhinane; Albrecht, Camille; Henry, Auberi; Sarazin, Thomas; Martiny, Laurent; El Btaouri, Hassan; Maurice, Pascal; Bennasroune, Amar; Romier‐Crouzet, Beatrice; Blaise, Sébastien; Duca, Laurent
Abstract : The Cardiovascular Continuum describes a sequence of events from cardiovascular risk factors to end‐stage heart disease. It includes conventional pathologies affecting cardiovascular functions such as hypertension, atherosclerosis or thrombosis and was traditionally considered from the metabolic point of view. This Cardiovascular Continuum, originally described by Dzau and Braunwald, was extended by O'Rourke to consider also the crucial role played by degradation of elastic fibers, occurring during aging, in the appearance of vascular stiffness, another deleterious risk factor of the continuum. However, the involvement of the elastin degradation products, named elastin‐derived peptides, to the Cardiovascular Continuum progression has not been considered before. Data from our laboratory and others clearly showed that these bioactive peptides are central regulators of this continuum, thereby amplifying appearance and evolution of cardiovascular risk factors such as diabetes or hypertension, of vascular alterations such as atherothrombosis and calcification, but also nonalcoholic fatty liver disease and nonalcoholic steatohepatitis. The Elastin Receptor Complex has been shown to be a crucial actor in these processes. We propose here the participation of these elastin‐derived peptides and of the Elastin Receptor Complex in these events, and introduce a revisited Cardiovascular Continuum based on their involvement, for which elastin‐based pharmacological strategies could have a strong impact in the future. Abstract : During aging and/or related processes an intense elastin remodeling is observed, which leads to the release of bioactive elastin‐derived peptides (EDP). These peptides drive both the development of cardiovascular risk factors and pathologies that profoundly influence the course of the cardiovascular continuum. In this review, we summarize the study of the biochemistry and biology of EDP, which leads to the definition of innovative pharmacological strategies.